Robotic versus laparoscopic distal pancreatectomy: multicentre analysis - Lof, S; van der Heijde, N; Abuawwad, M; Al-Sarireh, B; Boggi, U; Butturini, G; Capretti, G; Coratti, A; Casadei, R; D’Hondt, M; Esposito, A; Ferrari, G; et al. (British journal of surgery, 2021)
Abstract Background The role of minimally invasive distal pancreatectomy is still unclear, and whether robotic distal pancreatectomy (RDP) offers benefits over laparoscopic distal pancreatectomy (LDP) is unknown because large multicentre studies are lacking. This study compared perioperative outcomes between RDP and LDP. Methods A multicentre international propensity score-matched study included patients who underwent RDP or LDP for any indication in 21 European centres from six countries that performed at least 15 distal pancreatectomies annually (January 2011 to June 2019). Propensity score matching was based on preoperative characteristics in a 1 : 1 ratio. The primary outcome was the major morbidity rate (Clavien–Dindo grade IIIa or above). Results A total of 1551 patients (407 RDP and 1144 LDP) were included in the study. Some 402 patients who had RDP were matched with 402 who underwent LDP. After matching, there was no difference between RDP and LDP groups in rates of major morbidity (14.2 versus 16.5 per cent respectively; P = 0.378), postoperative pancreatic fistula grade B/C (24.6 versus 26.5 per cent; P = 0.543) or 90-day mortality (0.5 versus 1.3 per cent; P = 0.268). RDP was associated with a longer duration of surgery than LDP (median 285 (i.q.r. 225–350) versus 240 (195–300) min respectively; P < 0.001), lower conversion rate (6.7 versus 15.2 per cent; P < 0.001), higher spleen preservation rate (81.4 versus 62.9 per cent; P = 0.001), longer hospital stay (median 8.5 (i.q.r. 7–12) versus 7 (6–10) days; P < 0.001) and lower readmission rate (11.0 versus 18.2 per cent; P = 0.004). Conclusion The major morbidity rate was comparable between RDP and LDP. RDP was associated with improved rates of conversion, spleen preservation and readmission, to the detriment of longer duration of surgery and hospital stay.